Green Synthesis of Hierarchical H-ZSM-5 from Sugarcane Bagasse Silica and Application as Catalyst for Conversion of Cellulose into Glucose - Mita Rilyanti; Azizah Dewi Wahyu Ningrum; Ilim Ilim; Suharso Suharso; Mulyono Mulyono; Muhammad Ayoub; Wasinton Simanjuntak (Pandawa Institute, 2025)
In this study, a hydrothermal method was applied for the synthesis of hierarchical ZSM-5 from sugarcane bagasse ash (SCBA) as a precursor using starch as a green template. The synthesis was conducted by the hydrothermal method with the molar composition of 1.000:0.250:0.067:30.00 for SiO2:NaOH:Al(OH)3:H2O. For comparison, the synthesis without the use of a template was also conducted. The two zeolites synthesized were then tested as catalysts for glucose production by hydrolysis of cellulose derived from rice husk. The results indicate that starch served as an effective template for the formation of hierarchical ZSM-5 zeolite having mesopores with a surface area of 94.15 m2/g and pore diameter of 2.31 nm. The ZSM-5 synthesized with the use of a template was found to have a crystallinity of 76.33%, while the zeolite prepared without a template had a crystallinity of 79.25%. Hydrolysis experiments reveal that a glucose yield of 69.20% was achieved with the use of the H-ZSM-5 prepared with a template as a catalyst, while with the use of ZSM-5 prepared without a template the glucose yield of 42.42% was achieved. These different results justified the significantly higher performances of the ZSM-5 prepared with a template. Utilization of SCBA as raw material for the synthesis of hierarchical ZSM-5 zeolite is a part of the green chemistry initiative since this research converts the industrial waste into functional material. In addition, the utilization of SCBA is also ecologically beneficial because no excessive chemicals are required in the preparation process.